Kualifikasi Negarawan Sebagai Independensi Hakim Mahkamah Konstitusi di Indonesia - Lestari, Endriyani Lestari (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2023)
Constitutional court judges have different criteria than state officials in serving public authorities. There is no natural authority, other than the reaction of human formation as public officials in establishing laws for survival. The effectiveness of normative constitutional law, Pancasila, ethics and morality rest on the integration between legal readings and applicable morality. Thus, society surrenders its natural freedom to public authorities to obtain fair and appropriate decisions in line with the ethics of civil society and the laws of positivism. This study aims to reveal the characteristics of the independence of constitutional judges on the prerequisites of a statesman. The use of research methods based on normative research, statutory regulation approaches, comparative approaches, literature and doctrinal research objects. Judges of the constitutional court have different characteristics from other judges, because of the specifications of Article 24C paragraph (5) of the 1945 Constitution. The comparison of the morality of statesmen and individuals is based on applicable laws and the same standards. Professional public service requires competitive leadership, technical competency in processes, and ethics. The substance of the ethics of judges is independence which presents the responsibility of judges as part of public authority.